Comparison of incidence of complications and aesthetic performance for posterior metal-free polymer crowns and metal-ceramic crowns: results from a randomized clinical trial - Ohlmann, Brigitte; Lorenzo Bermejo, Justo; Rammelsberg, Peter; Schmitter, Marc; Zenthöfer, Andreas; Stober, Thomas (Journal of dentistry, 2014)
Objectives - The purpose of this randomized clinical study was to evaluate the clinical performance of posterior, metal-free polymer crowns after follow-up for up to six years, and to compare it with the performance of metal-ceramic crowns. - Methods - Eighty single crowns, manufactured from a polymer composite resin, were set on posterior teeth. Half of these received a glass-fibre framework (group 1) whereas half were prepared without framework stabilization (group 2). As the control group, 40 conventional metal-ceramic crowns were inserted. Primary endpoints were incidence of complications, investigated on a time-to-event basis, plaque status, and aesthetic performance. - Results - Thirty clinically relevant complications occurred after a median time of 2.3 years. Median follow-up time was four years. The most frequent complications were delamination (n=24) and root-canal treatment (n=4) of the crowns; the incidence of complications was not significantly different among crown materials (p=0.60). Twenty crowns had to be replaced (six polymer crowns in group 1, nine polymer crowns in group 2, four crowns in the control group, and one tooth (in group 1) had to be extracted). Mean plaque and gingival indexes for the test groups did not differ from those for the control group. - Conclusions - Within a median follow-up period of four years, the clinical performance of posterior polymer crowns with and without a glass-fibre framework was not significantly different from that of metal-ceramic crowns, although the number of catastrophic failures of composite crowns was higher than that of the metal-ceramic crowns. - Clinical significance - On the basis of the study results, posterior polymer crowns may be an alternative to metal-ceramic crowns, although additional research is needed before they can be recommended, without reservation, as permanent restorations.